The Role of Franchising on Industry Evolution : Assessing the Emergence of Franchising and its Impact on Structural Change - Beere, Rosalind (Springer Science and Business Media : Palgrave Macmillan, 2017)
The role of franchising on industry evolution is explored in this book both in terms of the emergence of franchising and its impact on industry structure. Examining literature and statistical information the first section provides an overview of franchising. The Role of Franchising on Industry Revolution then focuses on two core elements; the emergence or franchising and the contextual drivers prompting its adoption, and the impact of franchising on industry-level structural changes. Through two industry case studies, the author demonstrates how franchising has the ability to fundamentally transform an industry's structure from one of fragmentation to one of consolidation.
Keywords: Franchises (Retail trade); Business.; elektronické knihy; electronic books